Representation of Fatherhood and Emotional Growth in Inside Out - Nakesya Mayrani; Titis Setyabudi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study examines the representation of the father’s role and its contribution to children’s emotional development in the animated films Inside Out (2015) and Inside Out 2 (2024). Considering the influence of popular media on perceptions of family dynamics, the study analyzes how father figures are portrayed through narrative structure, cinematography, and visual symbolism. A descriptive, qualitative method with a systematic film-text analysis approach was employed. Data were collected from selected scenes, dialogues, and father–child interactions reflecting both explicit and implicit parenting patterns. The analysis integrates fatherhood theory, psychoanalytic perspectives, and theories of emotional development. Findings indicate that the father’s role is constructed through seven key dimensions: active involvement, accessibility, responsibility, emotional support, behavioral guidance, protective supervision, and affective communication. Among these, direct involvement and emotional support are the most significant in fostering children’s psychological growth.Furthermore, the films depict a shift in fatherhood from an authoritative, functional role to a more emotionally responsive presence. This transformation aligns with contemporary parenting paradigms and supports the development of children’s self-awareness, emotional regulation, empathy, and psychological integration. The study contributes to media studies and family psychology by emphasizing the importance of balanced representation of fathers in audiovisual content. It also highlights animated media as both entertainment and a reflection of evolving parenting values.